Toleransi dalam Keberagaman Masyarakat Desa Sumberbanjar Kecamatan Blubuk Kabupaten Lamongan - Intan Sari, Dewi; Muslimin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Tolerance is highly respected by the people of Sumberbanjar Village. The diversity of the people of Sumberbanjar Village is seen as a positive value for social life. The open attitude of the community to accept religious diversity shows mutual respect and respect for religious differences and the existence of adherents of other religions. The aims of this study were (1) to describe harmony tolerance in the diversity of the people of Sumbergondang Hamlet, Sumberbanjar Village, Bluluk District, Lamongan Regency. (2) To describe mutual cooperation tolerance in the diversity of the people of Sumbergondang Hamlet, Sumberbanjar Village, Bluluk District, Lamongan Regency. (3) To describe the Tolerance of Freedom to Perform Worship in the Diversity of the Community of Sumbergondang Hamlet, Sumberbanjar Village, Bluluk District, Lamongan Regency. (4) To describe the Tolerance of Accepting Differences in the Diversity of the Sumbergondang Hamlet, Sumberbanjar Village, Bluluk District, Lamongan Regency. In this study using a qualitative approach. Data collection methods used are observation, interviews, and documentation. Data analysis in this study was carried out by data reduction, data presentation, and conclusion drawing, and verification. The results obtained are (1) Respect for other residents of different religions can be witnessed when residents are holding a celebration, other residents of different religions are also invited. When there is news of the death of a member of the community, whether of the same religion or not, the public wants to take the time to offer their condolences. (2) During big occasions such as Eid al-Fitr, Eid al-Adha, Christmas or Easter, the youth of Sumbergondang Hamlet look after each other. The youth of the church guarded the security of the implementation of the Eid prayers, on the other hand during the Easter and Christmas services it was the bandits' turn to secure the worship. Mutual cooperation in terms of the success of the Alms Earth tradition is still carried out by the people of Sumbergondang Hamlet. (3) In religious practices in Sumbergondang Hamlet, where religious adherents have been able to carry out their religious activities safely and comfortably there is no prohibition or coercion from any party. (4) The people of Sumbergondang Hamlet, adherents of different religions mingle with each other, mutually accept each other's existence. Residential settlements that are close to each other, and places of worship in the middle of residential areas are not a problem. In addition, even though places of worship and religious activities are close to each other's homes, residents of other religions do not disturb the community